A new species of Miconia (Melastomataceae) from the high Andean forest of Bogotá D.C., Colombia - Mendoza-Cifuentes, Humberto (Instituto de Ecología, A.C., 2022)
Background and Aims: Miconia, with over 1900 species, is the largest exclusively Neotropical genus of woody vascular plants and one of the largest among flowering plants globally. During the development of the Flora de Bogotá project, an undescribed species of Miconia, unique among its congeners in terms of growth habit and trichome type, was found. The aim of this paper is to describe this new species so far known only from the surroundings of the Capital District and to compare it with the most morphologically similar taxa.Methods: The description and illustration of this new species were based on collections deposited in the JBB herbarium of the Botanical Garden of Bogotá. Vegetative and inflorescence measurements were made on dry herbarium material, while the floral and fruit measurements were obtained from rehydrated herbarium material. The conservation status is suggested based on the IUCN criteria.Key results: Miconia mahechae sp. nov. is characterized by the lianescent shrubby habit, oblong internodes, dense lanate indumentum of elongated moderately roughened trichomes on internodes, petioles and inflorescence, ovate to elliptical and 3-nerved leaves with obtuse to acute apex and smooth adaxial leaf surface, inconspicuous bracteoles, oblong-obovate anthers with an apical pore, and basal connective without appendages. Conclusions: This new species is morphologically close to M. ruizteranii; however, the new species differs by the shape of its anthers and the indumentum of stems and inflorescences. Miconia mahechae has been collected only in areas surrounding the city of Bogotá and the Chingaza and Sumapaz National Parks, in areas of the high Andean forest. Based on the IUCN criteria, we suggest its categorization as Vulnerable (VU).